HÉDI BOURAOUI’S LES JUMELLES DE L’ONCLE SAM : THE PILLARS OF AMERICAN SOCIETY - Sabiston, Elizabeth (Revue CMC Review, 2019)
The article analyzes the experimental novel of Hédi Bouraoui, Les Jumelles de l’oncle Sam (2017), paying particular attention to the metaphorical linkage between the destruction of the twin towers of the World Trade Center (9/ 11), and two women from different walks of American life whom a new immigrant comes to see as representative of America’s strengths and weaknesses.